Diffuse large B-cell lymphoma combined with two solid tumors: a case report - Zhang, Xiufang; Zhou, Shaojun; Zhou, Yuqiao; Qiu, Huiqing (Frontiers in Oncology, 2025)
We report a rare case of multiple primary tumors in a 67-year-old male. The patient was treated surgically for a lumbar disc herniation with intraoperative findings of L5 nerve root tumor, and postoperative pathology confirmed a diagnosis of diffuse large B-cell lymphoma (DLBCL). Three months later, the patient was further pathologically diagnosed with prostate cancer. The multidisciplinary treatment team devised a staged therapeutic strategy: firstly, 2 cycles of R-CHOP chemotherapy for DLBCL, followed by local radiotherapy for the residual lesion of lumbar spine tumor, and then 2 cycles of R-MTX-CHOP chemotherapy in sequence; after the DLBCL was controlled, the patient underwent radical prostatectomy, which was followed by adjuvant endocrine therapy and pelvic lymph node radiotherapy. Post-treatment evaluation showed complete remission (CR) in both tumors. After five years of disease-free survival, the patient presented with enlarged cervical lymph nodes in October 2022. A biopsy confirmed DLBCL recurrence. The treatment team administered six cycles of R-GemOx chemotherapy, followed by maintenance therapy with the targeted agent Orelabrutinib. Subsequent assessments confirmed a second CR. In September 2024, a colonoscopy revealed a rectal tumor, which was pathologically diagnosed as rectal cancer. The patient underwent radical surgery, and the pathological staging was determined to be stage I. According to the literature search, this is the first reported case of triple primary malignancies involving DLBCL, prostate cancer and rectal cancer, which provides valuable experience in the clinical diagnosis and treatment of such rare cases.